2016
DOI: 10.5301/ejo.5000764
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anterior Segment Parameters in Juvenile Diabetes Mellitus and Healthy Eyes

Abstract: Juvenile DM may affect anterior segment parameters and cause thicker LT, smaller PD, and lower AD. These effects may change the refractive status and should be considered during the examination of these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 18 publications
3
12
1
Order By: Relevance
“…The present study showed that the LT was significantly larger accompanied by the ACD decrease than that of the healthy children, which agree with the findings of Uzel et al [8]. A previous study of internal structure of lens performed with corrected Scheimpflug imaging by Wiemer et al [9] found that the lens was consisted of three cortical zones and the nucleus; in T1DM patients, all four layers rather than one typical layer of the lens were significantly thicker compared with those of the healthy control subjects, which supports the hypothesis that the thickening of the lens is the result of cellular or extracellular overhydration rather than insulin-induced mitogenesis of the epithelial cells.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The present study showed that the LT was significantly larger accompanied by the ACD decrease than that of the healthy children, which agree with the findings of Uzel et al [8]. A previous study of internal structure of lens performed with corrected Scheimpflug imaging by Wiemer et al [9] found that the lens was consisted of three cortical zones and the nucleus; in T1DM patients, all four layers rather than one typical layer of the lens were significantly thicker compared with those of the healthy control subjects, which supports the hypothesis that the thickening of the lens is the result of cellular or extracellular overhydration rather than insulin-induced mitogenesis of the epithelial cells.…”
Section: Discussionsupporting
confidence: 94%
“…It was noteworthy that despite LT and ACD significantly changed in T1DM children, no relation was found between the blood HbA1c level or DM duration and LT, ACD, and the other unchanged parameters (AL, SE, K1, K2, and CCT). Our study was in agreement with Uzel et al's [8], who found no relationship between LT and the HbA1c level in T1DM children. Several other studies have investigated the effect of DM duration or HbA1c level on ocular parameters.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These results are comparable to those from a similar study conducted in Turkey by Akinci et al [96]. However, other studies have not found this increase in CCT in children or young people with T1D [97, 98]. In another Turkish study in children with T1D, CCT was not shown to be associated with either the current fasting glucose level or duration of disease [99].…”
Section: Diabetes and Corneal Stromasupporting
confidence: 83%